Perspectives from the happiness literature and the role of new instruments for policy analysis - Bernard M. S. van Praag (Institute for the Study of Labor (IZA), 2007)
After having been ignored for a long time by economists, happiness is becoming an object of serious research in 21st century economics. In Section 2 we sketch the present status of happiness economics. In Section 3 we consider the practical applicability of happiness economics, retaining the assumption of ordinal individual utilities. In Section 4 we introduce a cardinal utility concept, which seems to us the natural consequence of the happiness economics methodology. In Section 5 we sketch how this approach can lead to a normative approach to policy problems that is admissible from a positivist point of view. Section 6 concludes
urn:nbn:de:101:1-20080425275
Keywords: 330; Lebenszufriedenheit; Lebensqualität; Wirtschaftspolitik